EFEKTIVITAS REGULASI HUKUM SIBER INDONESIA TERHADAP PENYALAHGUNAAN MEDIA SOSIAL UNTUK PROPAGANDA TERORISME - Raden Moch Fabian Haldiansyah; Angkasa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The development of information technology and social media has been utilized by radical and terrorist groups to spread propaganda, recruit members, and radicalize society, especially the younger generation. This study aims to analyze the effectiveness of cyber law regulations in Indonesia in dealing with terrorism propaganda through social media and identify obstacles in its implementation. The research method used is empirical juridical with a descriptive-analytical approach. Data were obtained through literature studies and interviews with Densus 88 AT Polri officers. The theories used are Donald J Black's theory of legal effectiveness and Lawrence M Friedman's theory of legal systems. The results of the study show that although Indonesia has several regulations such as the ITE Law and Law Number 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism, these regulations have not been effective in responding to the spread of radical propaganda in the digital space. The obstacles faced include the transnational nature of the internet, limited jurisdiction, anonymity of perpetrators, lack of specific regulations regarding intolerance and radicalism, and low digital literacy of the community. This study recommends the preparation of more comprehensive regulations, regarding existing social conditions.